Respuesta :
As per bernoulli's principle
[tex]P_1 + \frac{1}{2}\rho v_1^2 = P_2 + \frac{1}{2}\rho v_2^2[/tex]
here
[tex]P_1[/tex] = pressure upwards
[tex]P_2[/tex] = pressure downwards
[tex]v_1[/tex] = velocity of air upwards
[tex]v_2[/tex] = velocity of air downwards
now from this equation we can say that the pressure difference will be
[tex]P_1 - P_2 = \frac{1}{2}\rho v_2^2 - \frac{1}{2}\rho v_1^2[/tex]
now the force due to this pressure difference will be
[tex]F = (P_1 - P_2)A[/tex]
so this is the above force which is given above